2018
DOI: 10.1177/0954407018811195
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-order modeling of pressure excitation on automotive front side window

Abstract: The pressure excitation on automotive front side window acts as an indicator of the unsteady flow and wind noise in the front side window region. The complex unsteady flow in this area generates a wider range of vortex structures resulting in the nonhomogeneous and complex pressure excitation on side glass. The description of the pressure field, which can consider the nonhomogeneous in the exact space, is needed to better solve the vibration and noise problems. The turbulent pressure excitation on side window … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The numerical strategies of solving DES and acoustic wave equations based on APE have been used in previous works. 20 The resolution of time and space is the key to unsteady calculation and the key to solving the pressure fluctuation on the front side window. Based on the requirement of convergence, the Courant number becomes the link between the temporal resolution and the spatial resolution.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The numerical strategies of solving DES and acoustic wave equations based on APE have been used in previous works. 20 The resolution of time and space is the key to unsteady calculation and the key to solving the pressure fluctuation on the front side window. Based on the requirement of convergence, the Courant number becomes the link between the temporal resolution and the spatial resolution.…”
Section: Methodsmentioning
confidence: 99%
“…The hydrodynamic and acoustic pressure on the front side window were measured in the Aero-Acoustic Wind Tunnel (AAWT) in Shanghai Automotive Wind Tunnel Center (SAWTC). For details of the wind tunnel, readers can refer to Yuan et al 20 As shown in Figure 9(a), four surface microphones (Bru¨el & Kjaer 4949) were tapped on the outside surface of the front side window to measure the pressure fluctuation on the 2. According the discussion above, the efficient frequency range of the CFAT measurement here with the distance of the sensors D = 5 cm is (857, 3429) Hz.…”
Section: Acoustic Pressure Extraction Methods Based On Corrected Forc...mentioning
confidence: 99%
See 2 more Smart Citations
“…Through investigations done on passenger car, the noise caused by the rearview mirror has been investigated at a certain extent. 59 Because of the difference mentioned above, the conclusion drawn from passenger car cannot be extended to coach. As a result, how to understand the aerodynamic noise of rearview mirror area of coaches is the focus of this study.…”
Section: Introductionmentioning
confidence: 99%